STATUS KEBERLANJUTAN PENGELOLAAN EKOSISTEM MANGROVE DI KECAMATANTARUMAJAYA, KABUPATEN BEKASI - Abiyyu Muhammad Haris; Hartrisari Hardjomidjojo; Cecep Kusmana (Jurnal Analisis Kebijakan Kehutanan, 2021)
Mangrove ecosystems provide various useful types of products and services to support the life needs of coastal communities. In the management of sustainable mangrove ecosystems, it is necessary to integrate activities in the ecological, economic, and social dimensions as it is known in the concept of sustainable development. This study aims to measure the sustainability status of mangrove ecosystem management in Tarumajaya District, Bekasi Regency. Data analysis is applying RAPFISH with the multidimensional scaling (MDS) method. The results show that the sustainability status of mangrove ecosystem management in Tarumajaya District, Bekasi Regency, obtains a multidimensional index value of 45.79% with less sustainable status, index value; and the sustainability status in each dimension, is 21.72% for the ecological dimension (unsustainable), 49.15% for economic dimension (less sustainable), 40.68 % for social dimension (less sustainable), and 63.68% for institutional dimension (quite sustainable). The influencing factors for the sustainability of mangrove ecosystem management consist of 16 indicators from the 4 dimensions tested. The results of statistical parameter validation and the results of the Monte Carlo test show that all of the dimension indicators analyzed in the management of sustainability of mangrove ecosystems have a significant role in explaining the diversity of mangrove ecosystems dimensional index value and have a high level of confidence.